2017
DOI: 10.3892/or.2017.5893
|View full text |Cite
|
Sign up to set email alerts
|

HSP47 is associated with the prognosis of laryngeal squamous cell carcinoma by inhibiting cell viability and invasion and promoting apoptosis

Abstract: Abstract. Heat shock protein 47 (HSP47) is a 47 kDa collagen binding protein that has a close relationship with the development and progression of tumours. However, little is known concerning the expression profile of HSP47 in laryngeal squamous cell carcinoma (LSCC) patients and there is still insufficient data concerning the underlying mechanisms. The aim of the present study was to explore the expression of HSP47 in LSCC and provide an overview of its association with tumourigenicity and clinical prognosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
3
11
0
Order By: Relevance
“…Increased HSP47 expression in cancer cells promotes cancer progression in part by enhancing deposition of the ECM proteins [9], and several types of cancers are correlated with HSP47 expression in cancer cells [8][9][10]. The present study demonstrated that HSP47-positive broblasts in the stroma, but not HSP47positive cancer cells, were associated with recurrence of lung cancer after surgery.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Increased HSP47 expression in cancer cells promotes cancer progression in part by enhancing deposition of the ECM proteins [9], and several types of cancers are correlated with HSP47 expression in cancer cells [8][9][10]. The present study demonstrated that HSP47-positive broblasts in the stroma, but not HSP47positive cancer cells, were associated with recurrence of lung cancer after surgery.…”
Section: Discussionsupporting
confidence: 54%
“…[3][4][5][6][7] HSP47 has also been reported to be associated with several types of cancers, including cervical, breast, pancreatic, gastric, and colon cancer. [8][9][10][11] It is encoded by the SERPINH1 gene located on chromosome 11q13.5, and this region is one of the most frequently ampli ed in human cancer. [12] Several types of cancers are associated with abnormal protein folding, and HSP47 has been described as an important chaperone in the control and maintenance of cellular protein homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Increased HSP47 expression in cancer cells promotes cancer progression in part by enhancing deposition of the ECM proteins, [9] and several types of cancers are correlated with HSP47 expression in cancer cells. [8][9][10] The present study demonstrated that HSP47-positive fibroblasts in the stroma, but not HSP47-positive cancer cells, were associated with recurrence of lung cancer after surgery.…”
Section: Discussionsupporting
confidence: 46%
“…[3][4][5][6][7] HSP47 has also been reported to be associated with several types of cancers, including cervical, breast, pancreatic, gastric, and colon cancer. [8][9][10][11] It is encoded by the SERPINH1 gene located on chromosome 11q13.5, and this region is one of the most frequently amplified in human cancer. [12] Several types of cancers are associated with abnormal protein folding, and HSP47 has been described as an important chaperone in the control and maintenance of cellular protein homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, a number of molecules, such as TSR2, HSP47, snail, and so on were demonstrated to serve important roles in cellular processes including proliferation, differentiation, metastasis, and tumorigenesis in the prognosis of LSCC. [29][30][31][32][33] Tra2β, one of the human alternative splicing factors, is associated with cancer cell survival and therapeutic sensitivity, 34,35 but the regulatory role and regulatory mechanism of Tra2β in LSCC have remained elusive. In the present study, qRT-PCR and immunohistochemistry assays indicated that Tra2β was significantly upregulated in LSCC tissues compared with adjacent nontumorous tissues.…”
Section: Discussionmentioning
confidence: 99%